A novel fluorescent aptasensor based on gold and silica nanoparticles for the ultrasensitive detection of ochratoxin A. Issue 6 (21st January 2016) - Taghdisi, Seyed Mohammad; Danesh, Noor Mohammad; Beheshti, Hamed Reza; Ramezani, Mohammad; Abnous, Khalil
Abstract : Analytical approaches for the detection and quantitation of ochratoxin A (OTA) in blood serum and food products are high in demand. Abstract : Analytical approaches for the detection and quantitation of ochratoxin A (OTA) in blood serum and food products are high in demand. In this study, a fluorescent aptamer-based sensor (aptasensor) is developed for the selective and sensitive detection of OTA, based on a complementary strand of aptamer (CS) and two types of nanoparticles, gold nanoparticles (AuNPs) and silica nanoparticles (SNPs) coated with streptavidin. The fabricated aptasensor inherits the characteristics of SNPs, as enhancers of fluorescence intensity; AuNPs, such as large surface area and unique optical properties; and high affinity of the aptamer toward its target compared to its CS. In the absence of OTA, no FAM and biotin-labeled CS is in the environment of the SNPs coated with streptavidin, which leads to no fluorescence emission. In the presence of the target, an FAM and biotin-labeled CS-SNPs coated with streptavidin conjugate is formed, thus resulting in a very strong fluorescence emission. The designed fluorescent aptasensor exhibits high selectivity toward OTA with a limit of detection (LOD) as low as 0.098 nM. Furthermore, the fabricated aptasensor was successfully applied for the detection of OTA in grape juice and serum with LODs of 0.113 and 0.152 nM, respectively.